ANALYSIS OF WASTE MANAGEMENT FACTORS AS FLOOD MANAGEMENT EFFORTS IN LEU AND TAMBE VILLAGES, BIMA DISTRICT - Oktorina, Sarita; Sudanawati, Indri; Karami, Abdillah (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
Tambe Village and Leu Village are one of the villages in Bolo District with a population of 6600 people and 3728 people respectively (BPS, 2021). According to the Head of Bolo Sub-District, Mardianah, S.H said that “The most severe floods were in Leu Village, Tambe, SIgi Rato Village and Rasa Bou. (Islamudin, 2021). This study aims to determine the value of waste generation, density and composition of waste generated by the activities of the people of Tambe Village and Leu Village and the relationship between the level of community participation in Tambe Village and Leu Village in waste management. This study uses 2 methods, namely the Qualitative Method is carried out to collect data about attitudes, actions and knowledge of the community towards participation in waste management. Data was taken by using a questionnaire. Quantitative methods are used to collect data on waste generation and composition. Data is taken based on SNI 19-3964-1994. The value of waste generation and density generated by the activities of the Tambe Village community were 0.04 kg/person/day and 107.3 kg/m3 and in Leu Village 0.04 kg/person/day and 92.69 kg/m3. The results for the composition of the waste in Leu Village were 53.79 kg/day of food waste/leaves, 8.88 kg/day of paper, 0.16 kg/day of cloth, 17.31 kg/day of plastic, 0.37 kg/day of rubber. day, metal 0.05 kg/day, glass 0.05 kg/day, residue 1.38 kg/day, and wood 0.066 kg/day. The results for the composition of Tambe Village waste are 55.04 kg/day of food waste/leaves, 8.63 kg/day of paper, 0.27 kg/day of cloth, 15.84 kg/day of plastic, 0.51 kg/day of rubber. day, metal 0.52 kg/day, glass 0.05 kg/day, residue 1.68 kg/day, and wood 1.63 kg/day. There is a relationship between the level of community participation in Tambe Village and Leu Village in waste management. according to Spearman’s correlation with a significance level of 0.295 > 0.256 and 0.266 > 0.195 so that H0 is rejected.